2008
DOI: 10.1016/j.cam.2007.07.008
|View full text |Cite
|
Sign up to set email alerts
|

A new nonmonotone line search technique for unconstrained optimization

Abstract: In this paper, we propose a new nonmonotone line search technique for unconstrained optimization problems. By using this new technique, we establish the global convergence under conditions weaker than those of the existed nonmonotone line search techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…2, we slacken the nonmonotone F-rule of Sun et al [3] and introduce the nonmonotone slackness rule. The convergence of the line search algorithm based on the new rule is confirmed by virtue of [3] and [4] in Sect. 3.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…2, we slacken the nonmonotone F-rule of Sun et al [3] and introduce the nonmonotone slackness rule. The convergence of the line search algorithm based on the new rule is confirmed by virtue of [3] and [4] in Sect. 3.…”
Section: Introductionmentioning
confidence: 62%
“…However, subsequent studies showed that the convergence rate of monotone line search technique may reduce considerably when the iteration locates in a narrow curved valley. See [2][3][4] for details.…”
Section: Nonmonotone Line Search Slackness Rulementioning
confidence: 99%
See 2 more Smart Citations
“…This is important since, far from the solution, the likelihood of detecting a global solution instead of a local one is high when the merit function has a sufficient decrease, relative to the maximum merit values of previous iterations, of more than a certain quantity,η k . Similar nonmonotone F-rules for line search with guaranteed convergence in optimization context are available in the literature [37,41]. In [40], a nonmonotone trust region procedure using a filter methodology to handle the equality constraints of an optimization problem is presented.…”
Section: The Nonmonotone F-rulementioning
confidence: 99%